A simple economical atmometer for measuring evapotranspiration (ET) in greenhouse / Syarifah Nurul Aqilah Syed Mohd Damiri - Syed Damiri, Syarifah Nurul Aqilah (Faculty of Plantation and Agrotechnology, 2015)
This study aims to test the performance of simple economical atmometer, by watering the plant based on it, either it will give different result in term of yield, height of plant, number of leaves and fruiting time or there are no changes at all. This experiment was carried out for 50 days in medium technology greenhouse in UiTM Jasin, Melaka with the average temperature was 28°C to 32°C, average wind speed was 2km/h to 6km/h and the relative humidity was about 45% to 95% of saturation humidity. In this experiment, ET was measured using the simple economical atmometer and the chilli plant was irrigate based on it. This study also want to showed if there any significant different between the parameters. The result showed good performance of atmometer, also stated that there are no significant different in term of yield, height and number of leaves but there are significant different in term of fruiting time. On the other hand, in term of correlation, the result showed there was positive relationship and the yield can be estimated using the formula y = mx + c that obtain from the regression